Dual Inhibition and Safety Profiling of Padina Australis Extract as A Marine-Derived α-Glucosidase Modulator: An Integrated In Vitro and In Silico Study - Puspawati, Ni Made; Maharani, Putu Faraditha; Parwata, I Made Oka Adi; Budiari, Setyani; Patel, Rajesh K (Trends in Sciences, 2026)
Padina australis is a brown seaweed that shows promise as a natural source of α-glucosidase inhibitors for diabetes management. This study evaluated the α-glucosidase inhibitory activity of P. australis extracts and examined how extraction solvents influence this activity. It also identified potential active metabolites using gas chromatography–mass spectrometry (GC–MS), molecular docking, and toxicity prediction, thereby providing new evidence on the α-glucosidase inhibitory potential of P. australis. Ultrasonic-assisted extraction with n-hexane, ethyl acetate, and ethanol revealed that the ethyl acetate extract exhibited the highest inhibitory activity at 500 µg∙mL−1 (94.55 ± 0.16%), comparable to the ethanol extract (93.75 ± 2.56%) and higher than the n-hexane extract (45.37 ± 4.59%). GC–MS analysis identified 23 compounds, including loliolide, 2(4H)-benzofuranone, 5,6,7,7a-tetrahydro-4,4,7a-trimethyl, phytol, neophytadiene, and several fatty acids. Docking against yeast α-glucosidase (3A4A), human maltase–glucoamylase (3L4T), and lysosomal α-glucosidase (5NN6) indicated that loliolide and benzofuranone derivatives showed affinities approaching acarbose on the yeast enzyme, while neophytadiene and polyunsaturated fatty acids exhibited the most favorable interactions with the human intestinal enzyme. Binding to lysosomal α-glucosidase (5NN6) was consistently weaker, suggesting a degree of selectivity away from lysosomal targets. ProTox-3.0 predicted low acute toxicity for most metabolites (Classes V-VI) and moderate toxicity for two compounds (Class IV), whereas loliolide was classified as higher-risk (Class II). These findings support Padina australis as a potential source of α-glucosidase-modulating metabolites at a screening level. However, comprehensive studies including dose-response assays, enzyme kinetic characterization, fractionation, and toxicity testing are required to validate and extend these preliminary observations. HIGHLIGHTS Padina australis ethyl acetate extract showed in vitro α-glucosidase inhibition of > 90% at 500 µg∙mL−1. Molecular docking indicated strong binding of key metabolites to yeast (3A4A) and human intestinal (3L4T) α-glucosidase, with consistently weaker binding to the lysosomal isoform (5NN6), suggesting selectivity. GC–MS identified 23 compounds; key metabolites formed favorable interactions with catalytic site residues in docking simulations. In silico toxicity prediction indicated that most compounds were in low-toxicity classes (loliolide was a notable exception, flagged as higher toxicity). These findings support australis as a promising marine source of α-glucosidase-modulating metabolites, though further dose–response and safety studies are warranted. GRAPHICAL ABSTRACT